2006
DOI: 10.1007/s11664-006-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reflow and thermal aging on the microstructure and microhardness of Sn-3.7Ag-xBi solder alloys

Abstract: This work investigates the effect of reflow and the thermal aging process on the microstructural evolution and microhardness of five types of Sn-Ag based lead-free solder alloys: Sn-3.7Ag, Sn-3.7Ag-1Bi, Sn-3.7Ag-2Bi, Sn-3.7Ag-3Bi, and Sn-3.7Ag-4Bi. The microhardness and microstructure of the solders for different cooling rates after reflow at 250°C and different thermal aging durations at 150°C for air-cooled samples have been studied. The effect of Bi is discussed based on the experimental results. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…It was also already shown that bismuth and silver can have a significant impact on the corrosion properties in case of Sn-based solder alloy in NaCl solutions [17,18]. Furthermore, the influence of bismuth addition on the microstructure and the properties of Sn-rich SnAg lead-free solders has been also widely studied [13,[19][20][21][22][23]. However, the effect of bismuth on the corrosion behaviour in the case of micro-alloyed solder alloy is not deeply addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It was also already shown that bismuth and silver can have a significant impact on the corrosion properties in case of Sn-based solder alloy in NaCl solutions [17,18]. Furthermore, the influence of bismuth addition on the microstructure and the properties of Sn-rich SnAg lead-free solders has been also widely studied [13,[19][20][21][22][23]. However, the effect of bismuth on the corrosion behaviour in the case of micro-alloyed solder alloy is not deeply addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of bismuth to Sn-Ag alloys is believed to reduce the melting temperature, but wetting behavior and mechanical strength are degraded as well. [5][6][7] A certain amount of indium alloyed into Sn-Ag-Bi solder systems could decrease the melting point, and also improves the mechanical strength and the wetting ability. The compositions of the solders used in this study are 84Sn-3Ag-3Bi-10In and 89Sn-3Ag-3Bi-5In (in weight percent, and represented by 84-3-3-10 and 89-3-3-5 hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Bismuth has been reported as one type of addition to lower the melting temperature, increase the wettability, and improve the mechanical properties of solder alloys. [7][8][9][10][11][12][13][15][16][17] Our previous work reported that, with the addition of Bi into Sn-3.7Ag solders, the melting temperature decreased and the microhardness of Sn-Ag-xBi solders increased because Bi formed a solid solution with Sn and also Bi particles precipitated during the cooling process. 16 However, there is still a lack of knowledge about the effect of Bi on the interfacial reaction between leadfree solders and the Cu substrate, especially the relationship between the interfacial intermetallic compound (IMC) growth kinetics and the amount of Bi addition into the solders.…”
Section: Introductionmentioning
confidence: 99%